A low-molecular-weight angiogenic factor in cat retina. Issue 3 (March 1982) - Kissun, R D; Hill, C R; Garner, A; Phillips, P; Kumar, S; Weiss, J B
Abstract : A low-molecular-weight angiogenic factor has been isolated from healthy adult cat retinas. The factor, which has been purified by diethylaminoethyl (DEAE) cellulose chromatography and affinity chromatography, stimulates neovascularisation of the chick chorioallantoic membrane and has a number of properties similar to those previously described for a tumour factor. The finding of an angiogenic factor in healthy retina and its relationship to previously described inhibitors of angiogenesis is discussed.